Study on Pharmacodynamic Material Basis and Molecular Mechanism of Wutou Tang in Pain Relief Based on Computer Simulation - Chunsong ZHENG; Jie LIN; Changlong FU; Jinxia YE; Xiaojie XU; Hongzhi YE (康复学报)
Objective: To explore pharmacodynamic material basis and molecular mechanism of Wutou Tang in pain relief. Methods: Based on the simulation platform of Discovery Studio, the molecular set of Wutou Tang was built and compared with drug set of anti-inflammatory and analgesic actions from DrugBank database in chemical space. After that, network pharmacology based on molecular docking was used to explore the interactions of Wutou Tang and targets related to pain. Results: The molecular sets of Wutou Tang and drugs had better overlaps in chemical space. The main pharmacodynamic material basis of Wutou Tang contains alkaloids, flavonoids, saponins. They could act on six targets including inducible nitric oxide synthase (iNOS), p38, C-Jun N-terminal Kinase 1 (JNK-1), tumor necrosis factor-α (TNF-α), phosphodiesterase 4A (PDE-4A) and Kappa-type opioid receptor. Conclusion: Wutou Tang can mainly act on p38 MAPK and JNK signaling pathways, and has multiple analgesic actions including the inhibition of NO release, the reduction of mechanical hyperalgesia, and the prevention of algesia impulsion conduction and transmission, etc. It has an effect of multi-ingredients, multi-targets and multi-pathways.